2014
DOI: 10.4097/kjae.2014.66.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Torsade de pointes in liver transplantation recipient after induction of general anesthesia: a case report

Abstract: Torsade de pointes (TdP) is an uncommon and specific form of polymorphic ventricular tachycardia, associated with a prolonged QT interval. Prolongation of the QT interval is the most widely recognized electrophysiological abnormality in patients with liver cirrhosis. We observed a case of TdP leading to cardiopulmonary resuscitation after the induction of general anesthesia, in a patient with liver cirrhosis scheduled for emergency cadaveric donor liver transplantation. The patient had mild QT prolongation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Although investigators evaluating the effect of prolonged QTc on mortality in cirrhotic patients have reported conflicting results, none has evaluated its effect on outcomes after OLT . Despite anecdotal reports of life‐threatening arrhythmias occurring in patients with prolonged QTc during OLT, it is certainly an uncommon occurrence. However, abnormal cardiac repolarization might indirectly contribute to mortality during stressful scenarios like surgery or infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigators evaluating the effect of prolonged QTc on mortality in cirrhotic patients have reported conflicting results, none has evaluated its effect on outcomes after OLT . Despite anecdotal reports of life‐threatening arrhythmias occurring in patients with prolonged QTc during OLT, it is certainly an uncommon occurrence. However, abnormal cardiac repolarization might indirectly contribute to mortality during stressful scenarios like surgery or infection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, halogenated volatile anesthetics (halothane, enflurane, isoflurane, desflurane, sevoflurane) are among the drugs that cause QTc interval prolongation, and they should therefore be avoided in anesthetic procedures in LQTS and liver cirrhosis patients, due to the increased risk of perioperative malignant ventricular arrhythmias [31]. Recently, Chung et al presented a case report on a patient with liver cirrhosis scheduled for emergency cadaveric donor liver transplantation who developed TdP after sevoflurane use during general anesthesia [32]. Di Micoli et al showed TdP in a patient with decompensated liver cirrhosis during amiodarone infusion because of new-onset atrial fibrillation [33].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Bal and Thuluvath observed no survival differences in patients with and without prolonged QTc interval, but life-threatening ventricular arrhythmia is reported consequent to a prolonged QTc interval in cirrhosis during stress. [ 1 2 3 4 ] In our recipient, pre-operative prolonged QTc interval (470 ms) increased to peak in neohepatic phase (625 ms). Multiple blood transfusions could have led to hypomagnesaemia at the cellular levels, contributing to rhythm disorder.…”
mentioning
confidence: 72%
“…Torsade de pointes is reported at varied stages (after anaesthetic induction, dissection phase, caval clamping in anhepatic or portal vein unclamping in neohepatic phase) of liver transplantation. [ 2 3 ] Amiodarone, 5-HT3 antagonists and sevoflurane may prove detrimental by aggravating QTc prolongation. [ 3 ] A list of known drugs to cause QTc prolongation is shown in Table 1 .…”
mentioning
confidence: 99%